A Rapid and Sensitive Diagnosis of Typhoid Fever Based On Nested PCR-Voltammetric DNA Biosensor Using Flagellin Gene Fragment - Yeni Wahyuni Hartati; Santhy Wyantuti; M. Lutfi Firdaus; Nurul Auliany; Rini Surbakti; Shabarni Gaffar (Indonesian Journal of Chemistry, 2016)
Typhoid fever caused by Salmonella typhi is an important issue for public health in the world. Laboratory methods for rapid and sensitive diagnosis are very important for disease management. The purpose of this study was to determine the performance of nested PCR–voltammetric DNA biosensor using flagellin gene (fla) of S. typhi as a marker. The differential pulse voltammetry using pencil graphite electrode was applied to measure the guanine oxidation signal of probes vs synthetic target stDNA and probes vs fla PCR product hybridizations. The probe DNA selectivity was examined by hybridized probes vs non-complementary sequence. The result showed that the first round nested PCR product can not be visualized by agarose electrophoresis, whereas using the voltammetric biosensor methods can be detected both for the first or second round nested PCR product. The average peak current of hybridized probe vs first and second round of PCR product was 2.32 and 1.47 μA respectively, at 0.9 V. Detection of the DNA sequences of the infectious diseases from PCR amplified real sample was also carried out using this voltammetric DNA biosensor methods.